2022
DOI: 10.1094/pdis-11-21-2610-fe
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Calonectria Diseases on Ornamental Horticulture: Diagnosis and Control Strategies

Abstract: Diseases caused by fungi in the genus Calonectria pose a significant threat to the ornamental horticulture industries in Europe and the United States. Calonectria spp. are particularly challenging pathogens to manage in ornamental production systems and the urban landscape for multiple reasons. A high level of species diversity and poorly resolved taxonomy in the genus makes proper pathogen identification and disease diagnosis a challenge, though recent molecular phylogenetic studies have made significant adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 96 publications
0
4
0
1
Order By: Relevance
“…The morphologically similar Calonectria henricotiae was distinguished as a separate genetic grouping in 2005 (Gehesquière et al 2014) and identified as a separate species in 2016 (Gehesquière et al 2016). It is known to occur in Germany, Belgium, the United Kingdom, Slovenia and the Netherlands (Gehesquière 2014;Gehesquière et al 2016) as well as the Czech Republic but has not been reported from North America, Asia or New Zealand to date (Hall et al 2021;Aiello et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The morphologically similar Calonectria henricotiae was distinguished as a separate genetic grouping in 2005 (Gehesquière et al 2014) and identified as a separate species in 2016 (Gehesquière et al 2016). It is known to occur in Germany, Belgium, the United Kingdom, Slovenia and the Netherlands (Gehesquière 2014;Gehesquière et al 2016) as well as the Czech Republic but has not been reported from North America, Asia or New Zealand to date (Hall et al 2021;Aiello et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Calonectria includes a range of important plant pathogens that are widely distributed in tropical, subtropical, and temperate regions throughout the world [ 1 , 2 , 3 ]. These aggressive pathogens can infect approximately 335 plant species residing in 100 plant families, including important agricultural, horticultural, and forestry crops [ 1 , 2 , 3 , 4 ]. Leaf blight caused by Calonectria species is considered one of the most prominent diseases of Eucalyptus plantations in China, Brazil, Colombia, Vietnam, and other countries [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…La integración de fungicidas con la solarización del suelo mostró una menor severidad del "damping off" en el cultivo de ají (Kadam et al, 2018). El dazomet se ha usado en los viveros como alternativa química al bromuro de metilo, encontrándose una reducción significativa sobre la incidencia de enfermedades fúngicas transmitidas por patógenos habitantes del suelo, como lo son los géneros Rhizoctonia y Cylindrocladium (Aiello et al, 2018;Santori et al, 2020;Villarino et al, 2021;Aiello et al, 2022).…”
Section: Resultados Y Discusiónunclassified